Venetoclax, bendamustine, and rituximab in patients with relapsed or refractory NHL: a phase Ib dose-finding study. (28th July 2018) - de Vos, S; Swinnen, L J; Wang, D; Reid, E; Fowler, N; Cordero, J; Dunbar, M; Enschede, S H; Nolan, C; Petrich, A M; Ross, J A; Salem, A H; et al.
Abstract: Background: Venetoclax is a selective, potent inhibitor of the anti-apoptotic B-cell leukemia/lymphoma-2 protein approved for treatment of chronic lymphocytic leukemia. We conducted a dose-finding study of venetoclax in combination with bendamustine–rituximab (BR) in patients with relapsed/refractory non-Hodgkin's lymphoma (NHL). Patients and methods: BR was given for six cycles at standard doses. Intermittent and continuous oral venetoclax administration was explored at 50–1200 mg daily doses. Co-primary objectives included safety, pharmacokinetics (PKs), maximum-tolerated dose (MTD), and recommended phase II dose (RP2D); secondary objective was preliminary efficacy. Results: Sixty patients were enrolled: 32 with follicular lymphoma, 22 with diffuse large B-cell lymphoma, and 6 with marginal zone lymphoma. Nausea (70%), neutropenia (68%), diarrhea (55%), and thrombocytopenia (52%) were the most frequent adverse events (AEs). Most common grade 3/4 AEs were neutropenia (60%) and lymphopenia (38%). Serious AEs were reported in 24 patients; the most frequent were febrile neutropenia and disease progression (8% each). Five patients died from either disease progression ( n  = 4) or respiratory failure ( n  = 1). MTD was not reached; RP2D for venetoclax-BR combination was established as 800 mg daily continuously. Venetoclax PK exposure with and without BR was comparable. For all patients, overall response rate was 65%. Median duration of overall response, overall survival, and progression-free survival was 38.3 months [95% confidence interval (CI) 10.4–NR], not yet reached, and 10.7 months (95% CI 4.3–21.0), respectively. Conclusions: This study established the safety profile of venetoclax in combination with BR, and results demonstrated tolerability and preliminary efficacy of the combination. Additional follow-up is needed to better determine the future role of BR plus venetoclax in the treatment of relapsed/refractory B-cell NHL. Trial registered: Clinicaltrials.gov, NCT01594229.